Automated manufacturing - Gardner, Leonard B.; ASTM. Committee E-31 on Computerized Systems; International Symposium on Automated Integrated Manufacturing (1st : 1983 : San Diego, Calif.) (Philadelphia, PA : ASTM, 1985)
22